Management And Training Programs Of Military Drone Small Unmanned Aircraft Systems. (September 2017) - Roberts, Eric; Beck, Andrew
The present study investigated the operational readiness of Army unmanned aircraft systems (UAS) training programs. Small unmanned aircraft systems (SUAS), unlike larger UAS, are not managed by the Aviation branch within the Army. They are managed and employed by Infantry branch unit personnel. The differences in organizational culture and methods between the Infantry and Aviation could pose challenges for safe SUAS utilization. This study found that the majority of SUAS operators were not meeting flight currency requirements as per Army regulation. A high number of respondents believed that SUAS would be more effectively and safely employed if SUAS was its own military occupational specialty (MOS) and was managed by Aviation branch. This study helps us to understand the occupational demands of unmanned aircraft systems warrant consideration of a SUAS MOS, which is branched in Aviation.